Parenteral versus oral administration of systemic antimicrobials in European nursing homes: a point-prevalence survey. - Broex, Elisabeth; Boudewijn Catry; Katrien Latour; Karl Mertens; Vankerckhoven, Vanessa; Muller, Arno; Stroobants, Rudi; Zarb, Peter; Goossens, Herman; Beatrice Jans (Drugs Aging, 2011)
BACKGROUND: Residents in long-term care facilities are predisposed to healthcare-associated infections that are likely caused by antimicrobial-resistant micro-organisms. Long-term care facilities are increasingly able to offer parenteral antimicrobial treatment but there are few data on the use and appropriateness of such treatment in this setting. Information on the use of parenteral antimicrobials and associated factors in long-term care facilities is necessary to assess the risks and benefits of this treatment and to support the development of antimicrobial policies aimed at minimizing the emergence and spread of antimicrobial resistance. OBJECTIVE: The aim of this study was to describe the extent of parenteral and oral antimicrobial use in participating European nursing homes (NHs) and to analyse the resident characteristics and determinants associated with route of antimicrobial administration. METHODS: Data on resident characteristics and antimicrobials were collected by means of a point-prevalence survey. Logistic regression was used to analyse the data. RESULTS: Based on data from 21 European countries for 2046 antimicrobial prescriptions, an average of 9.0% (range by country: 0.0-66.7%) of treatment was administered parenterally. Multivariate analysis showed that residents receiving parenteral antimicrobials had greater morbidity, such as increased risk of having a urinary catheter (p < 0.001), a vascular catheter (p < 0.001), impaired mobility (p = 0.007) and disorientation (p = 0.005). Residents receiving parenteral antimicrobials also had been admitted more recently into the NH (p = 0.007). Empirical treatment of respiratory tract infections (RTIs) accounted for the majority of parenteral antimicrobials, while prophylaxis of urinary tract infection (UTI) was the most common indication for oral antimicrobials. Beta-lactam antibacterials (cephalosporins and aminopenicillins) were the predominant classes used. CONCLUSIONS: Our study showed that risk and care-load factors (i.e. the presence of a urinary or vascular catheter, impaired mobility, disorientation and relatively short length of stay) were associated with parenteral administration of antimicrobials in NHs. Furthermore, both the indication and the class of antimicrobial agent used were associated with administration route. For empirical treatment of RTIs, antimicrobials were most often administered parenterally.
Keywords: Administration, Oral; Aged, 80 and over; Anti-Infective Agents; Data collection; Drug Prescriptions; Europe; Female; Homes for the Aged; Humans; Male; nursing homes